Implementasi Komputasi Paralel untuk Optimalisasi Komputasi Pada Aplikasi Transliterasi Huruf Latin ke Aksara Jawa - Syauqi, Ala; Hidayah, Anis Nurul (JOIN (Jurnal Online Informatika), 2018)
Javanese script is one of the ancestral heritage of Indonesia that must be preserved. Nowadays javanese script is increasingly abandoned, since latin writing is often used in daily activities. This is become worse by student difficulties of learning to read and write javanese script because the methods are less attractive for example teacher centered learning. One of solution to solve this problem is interactive latin to javanese script transliteration application. Research on the latin to javanese script transliteration has been produced various applications such as JawaTex, Hanacaraka, and Pandawa. From these three applications is showed that the Pandawa application with decision tree method has the highest level of accuracy. However, the computational time required by this application method is also highest than other applications. The more transliterated text is conduct the longer process time is used. This research aims to shorten Pandawa application computing time with parallel computing method without modifies decesion tree algorithm. Parallel computing is implemented with multithread on java programming language to perform the process of latin into javanese script transliteration simultaneously. Experimental results obtained that the implementation of multithread in decicion tree method for latin into javanese script transliteration reduce the average computation time up to 97.05%.